Heterogeneity of Grid Emission Factor Accounting in China: Temporal Resolution, Spatial Resolution, and Energy Distribution - Dong Hongchuan; Gu Ye; Zhang Jihong (E3S Web of Conferences)
Grid emission factor has become the most critical variable in carbon market quota allocation and carbon footprint accounting of international trade products. Different grid emission factors will lead to great differences in carbon emissions of enterprises or products. It is found that the temporal resolution, spatial resolution and energy distribution of cogeneration have great influence on the emission factors of power grid. This paper uses the data of China’s power industry to carry out empirical analysis. For each dimension, we set different choices and explore their specific impacts. It is found that the different choices of the three dimensions will cause 5.01%, 20.59%, 4.38% differences in the calculation results of grid emission factors. Finally, based on the research results, this paper puts forward suggestions from three aspects: authoritative guidance, data accuracy and international communication, in order to provide reference for Scope 2 greenhouse gas emissions accounting and reporting.